Biogeochemical Activity of Pasture Plant Species in the Absorption of Lead, Cadmium, and Arsenic under the Conditions of the Volgograd Region - Belozubova, N. Yu; Zubkova, V. M. (Arid ecosystems, 2021)
The production of livestock products in suburban areas of urban agglomerations, including the steppes of the Sarpinskaya lowland, a territory favorable for animal husbandry, is economically profitable due to the proximity of processing enterprises and consumers. At the same time, such zones are subject to the aerial technogenic impact of urban industrial enterprises, which are sources of heavy metals and arsenic that enter the ecosystems. In this regard, the study of the distribution of pollutant elements in agrocenoses adjacent to industrial centers is becoming increasingly important. The biogeochemical activity was studied for plants belonging to the families of legumes (Fabaceae), including the sweet clover ( Melilotus officinalis (L.) Pall.), and white sweet clover ( Melilotus albus (Medik.) H. Ohashi & Y. Tateishi); cereals (Poaceae), including creeping wheatgrass ( Elytrigia repens (L.) Nevski), desert wheatgrass ( Agropyron desertorum (Fisch.) Schultes), and southern reeds ( Phragmites australis (Cav.) Trin. ex Steud.); and haze (Chenopodiaceae), including spreading quinoa ( Atriplex patula L.). There was a high degree of arsenic accumulation by the roots of all studied plants, with the exception of medicinal sweet clover ( Melilotus officinalis ); the highest biogeochemical activity in the uptake of lead, cadmium and arsenic in the aboveground part was found in spreading swans ( Atriplex patula ) and the roots of the desert wheat ( Agropyron desertorum ).